Creativity Meets Technology: The Role of AI Poem Generator in Enhancing Students’ Writing Skills - Hanifah Azhari; Samsul Khabib (Universitas Islam Negeri Palopo, 2026)
This study examines English course students' perceptions and experiences with AI poetry generators in descriptive poetry learning. Despite growing use of technology in language education, there is limited understanding of its impact on students' creative writing, especially in Indonesia's EFL context. This qualitative case study, conducted in Gresik, East Java, involved 10 students and used interviews, classroom observations, focus groups, and poetry analysis over two months. The findings suggest students engage positively with AI tools, improving their vocabulary and confidence, though they face challenges with technical infrastructure and cultural relevance. This research provides insights into AI’s role in creative writing education and highlights the importance of cultural adaptation in EFL contexts.